Assessment of immunization coverage during COVID-19 pandemic among 12-23 months old children in Sonitpur district under Bihaguri BPHC of Assam - Banik, Souvik; Baruah, Rupali; Chakraborty, Shashanka Shekhar (International Journal Of Community Medicine And Public Health, 2024)
Background: The longest-lasting decline in childhood vaccination rates in a generation is seen during COVID-19 Pandemic in India. The study aims to analyze the overall scenario of Immunization coverage of 12-23 months children in Sonitpur under sub-centers of Besseria State Dispensary under Bihuguri BPHC during COVID-19 pandemic. Methods: All the children registered with mother and child protection card in villages under Besseria State Dispensary under Bihuguri BPHC, Sonitpur during COVID-19 pandemic were surveyed for a period of two months from May and June 2021. A simple random sampling method of study includes 84 respondents of children in the age group of 12-23 months. Results: A total of 84 respondents were surveyed. All the cases include children between the ages of 12 and 23 months. 96.25% babies received BCG at birth. 80% received OPV 0 dose. Hepatitis B was given to 76.25%. 100% of the babies received 3 dosages of OPV at 6, 10, and 14 weeks, only 21 (26.25%) received PCV 1st dose, 24 (30%) received PCV 2nd dose, 23 (28.75%) received PCV booster dose. 65% of the children between 12 and 23 months old received all the vaccinations. Conclusions: The restriction and the quarantine implemented during the COVID-19 pandemic has hampered the immunization status of the children. The non-availability of vaccines has delayed the immunization status. Comprehensive training and supervision of health workers, increasing awareness regarding immunization sessions, and vaccine preventable disease (VPD) are some of the interventions which could help tackle the issue.